WORKSHOP PENYUSUNAN BOOKLET PEMBELAJARAN NUMERASI SESUAI LEVEL KEMAMPUAN SISWA BAGI PENGAWAS SD/MI - Affandi, Lalu Hamdian; Hidayati, Vivi Rachmatul; Erfan, Muhammad; Oktaviyanti, Itsna; Husniati, Husniati (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2024)
Implementation of Kurikulum Merdeka has been focused on creating students’ characteristics-based learning, particularly in numeracy learning. Accomplishment of such mission requires supervisor involvement. So far, Kurikulum Merdeka piloting only focused on teacher competency improvement with little attention to supervisor involvement. Present workshop is aimed at increasing supervisor readiness for supporting numeracy learning which is based on students’ prior ability. Present workshop was attended by 17 representatives of SD/MI supervisor in District of Lombok Tengah. The workshop was conducted by means of oral presentations, class discussions, small group discussion, and group presentation. The workshop resulted 4 drafts of prior ability-based booklets. The booklets are expected to improve students’ early numeracy skills. However, the booklets are not variative enough to accommodate various essential learning materials in numeracy learning. Therefore, continuous collaboration is necessary for ensuring effective numeracy learning in the era of Kurikulum Merdeka.